2008
DOI: 10.1021/ic7018346
|View full text |Cite
|
Sign up to set email alerts
|

New Fluorogenic Dansyl-Containing Calix[4]arene in the Partial Cone Conformation for Highly Sensitive and Selective Recognition of Lead(II)

Abstract: A new efficient and highly selective fluorescent chemosensor for determination of Pb (2+) has been obtained by covalent attachment of two pendent proton-ionizable dansylcarboxamide groups to the calix[4]arene preorganized in the partial cone conformation. This geometry of the calixarene moiety was chosen on the basis of the prior (1)H NMR study of conformations adopted by the flexible dansyl-containing prototype upon complexation with lead ion. In acidic MeCN-H2O (1:1 v/v) solutions, the partial cone fluoroion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 34 publications
(28 reference statements)
1
23
0
Order By: Relevance
“…Lu and co-workers utilized gold nanoparticles and DNAzyme as a unique class of biosensors for Pb 2+ [8], while Kwon et al reported a new fluorescent sensor based on rhodamine B for Pb 2+ [9]. In addition, some fluorophore-appended macrocycles have also been reported [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Lu and co-workers utilized gold nanoparticles and DNAzyme as a unique class of biosensors for Pb 2+ [8], while Kwon et al reported a new fluorescent sensor based on rhodamine B for Pb 2+ [9]. In addition, some fluorophore-appended macrocycles have also been reported [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The preferred geometry in solution may be determined by NMR spectroscopy applied to the metal complex of the flexible ligand. In particular, in complexes with Hg 2þ , mobile calix [4]arene N-dansylcarboxamide 1 was found to prefer the cone (62) and, under different experimental conditions, 1,3-alternate conformation (44).…”
Section: N-dansylcarboxamidesmentioning
confidence: 96%
“…Known metal-sensing dansyl-containing fluorogenic calixarenes (as well as thiacalixarenes) vary in the fashion of the fluorophore attachment to the receptor moiety as HN-dansyl (37,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and O-dansyl ligands (36,(55)(56)(57) (for the structural formulae, see Figures 1-4). In the former type, the anchor NH-group usually is a part of carbamoyl or aminoalkyl linker, or it may be bound directly to the aromatic ring of the calixarene; while in the latter type, the dansyl moiety is a substituent on the calixarene lower-rim phenolic oxygen.…”
Section: General Characteristics Of Dansyl-containing Calixarene-basementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, thiacalix[n]arene and its functionalised derivatives behave as extractants for metal ions and can form host -guest complexes. Their aforementioned interactions make it possible to use them for sensing (10,11), solvent extraction (5, 6, 12 -20), gas adsorption and molecule storage (21 -24). In addition, thiacalix [n] arenes are superior to common calix[n]arenes because they possess higher molecular structure flexibility and metal ion affinity.…”
Section: Introductionmentioning
confidence: 99%